Toll-Like Receptor 2 Mediates In Vivo Pro- and Anti-inflammatory Effects of Mycobacterium Tuberculosis and Modulates Autoimmune Encephalomyelitis - Piermattei, Alessia; Migliara, Giuseppe; Di Sante, Gabriele; Foti, Maria; Hayrabedyan, Soren Bohos; Papagna, Angela; Geloso, Maria Concetta; Corbi, Maddalena; Valentini, Mariagrazia; Sgambato, Alessandro; Delogu, Giovanni; Constantin, Gabriela; et al. (Frontiers in Immunology, 2016)
Mycobacteria display pro- and anti-inflammatory effects in human and experimental pathology. We show here that both effects are mediated by Toll like receptor 2 (Tlr2), by exploiting a previously characterized Tlr2 variant (Met82Ile). Tlr2 82ile promoted self-specific pro-inflammatory polarization as well as expansion of ag-specific FoxP3+ Tregs, while Tlr2 82met impairs the expansion of Tregs and reduces the production of IFN-γ and IL-17 pro-inflammatory cytokines. Preferential dimerization with Tlr1 or Tlr6 could not explain these differences. In silico, we showed that Tlr2 variant Met82Ile modified the binding pocket for peptidoglycans and participate directly to a putative binding pocket for sugars and Cadherins. The distinct pro- and anti-inflammatory actions impacted on severity, extent of remission and distribution of the lesions within the Central Nervous System of Experimental Autoimmune Encephalomyelitis. Thus, Tlr2 has a janus function in vivo as mediator of the role of bacterial products in balancing pro- and anti-inflammatory immune responses.